Hubungan persepsi kepercayaan dalam pemberian ASI eksklusif dengan pencegahan stunting - Nurazila, Nurazila; Fajar, Nur Alam; Sari, Yona Wia Sartika; Amalia, Risa Nur (Holistik Jurnal Kesehatan, 2025)
Background: Stunting is a public health problem that is of global concern, especially in developing countries. This condition is characterized by failure to thrive in children due to chronic malnutrition, recurrent infections, and suboptimal parenting practices. Exclusive breastfeeding for the first six months of a baby's life is recommended by WHO and the Indonesian Ministry of Health as an effort to meet the nutritional needs of babies and protect them from infectious diseases. Breast milk contains all the nutrients needed by babies to grow and develop optimally. However, the level of exclusive breastfeeding in Indonesia is still far from the national target of 70%. One of the factors that influences the low practice of exclusive breastfeeding is the mother's perception and belief in the benefits of breast milk. Purpose: To determine the relationship between the perception of belief in exclusive breastfeeding and the prevention of stunting. Method: Quantitative research with a cross-sectional correlation design to determine the relationship between the perception of belief in exclusive breastfeeding and the prevention of stunting. The population in this study were mothers who have children aged 6–24 months in Banyuasin Regency. The sampling technique used the proportional stratified random sampling method and obtained a sample size of 108 respondents. The instrument used was a questionnaire sheet given to respondents and data analysis using univariate and bivariate Chi-Square analysis or Spearman correlation test. Results: Most respondents aged 20-35 years as many as 88 (83.0%) with the last education ≥ high school as many as 72 respondents (67.9%), as many as 99 respondents (93.4%) did not work, had children > 2 children as many as 69 respondents (65.1%), family income more ≥ UMR as many as 87 respondents (82.1%), as many as 79 respondents (74.5%) had good knowledge about exclusive breastfeeding, and most respondents provided exclusive breastfeeding as many as 69 respondents (65.1%). Based on the variable of perception of trust (Perceived Susceptibility, Severity, Benefit, and Barriers), the results of the statistical test p value <0.05, indicating a significant relationship between perception of trust and exclusive breastfeeding. Conclusion: There is a significant relationship between perception of mother's trust and the practice of exclusive breastfeeding with efforts to prevent stunting. Children who receive exclusive breastfeeding for the first six months have a lower risk of experiencing stunting, characterized by better physical growth and cognitive development. This shows that exclusive breastfeeding is not only a nutritional strategy, but also a long-term preventive measure against stunting.   Keywords: Exclusive Breastfeeding; Perception; Stunting; Trust.   Pendahuluan: Stunting merupakan salah satu masalah kesehatan masyarakat yang menjadi perhatian global, terutama di negara-negara berkembang. Kondisi ini ditandai dengan gagal tumbuh pada anak akibat kekurangan asupan gizi kronis, infeksi berulang, dan praktik pengasuhan yang kurang optimal. ASI eksklusif selama 6 bulan pertama kehidupan bayi merupakan rekomendasi dari WHO dan Kementerian Kesehatan Indonesia sebagai upaya untuk memenuhi kebutuhan gizi bayi dan melindungi mereka dari penyakit infeksi. ASI mengandung semua nutrisi yang diperlukan bayi untuk tumbuh dan berkembang secara optimal. Namun, tingkat pemberian ASI eksklusif di Indonesia masih jauh dari target nasional. Salah satu faktor yang memengaruhi rendahnya praktik pemberian ASI eksklusif adalah persepsi dan kepercayaan ibu terhadap manfaat ASI. Tujuan: Untuk mengetahui hubungan persepsi kepercayaan dalam pemberian ASI eksklusif dengan pencegahan stunting. Metode: Penelitian kuantitatif dengan menggunakan desain cross-sectional correlation. Populasi dalam penelitian ini adalah ibu yang memiliki anak usia 6–24 bulan di Kabupaten Banyuasin. Teknik pengambilan sampel menggunakan metode proportionate stratified random sampling dan didapatkan jumlah sampel sebanyak 108 responden. Instrumen yang digunakan berupa lembar kuesioner yang diberikan kepada responden dan analisis data menggunakan analisis univariat dan bivariat chi-square atau uji korelasi Spearman. Hasil: Sebagian besar responden berusia 20-35 tahun sebanyak 88 (83.0%) dengan pendidikan terakhir ≥SMA sebanyak 72 responden (67.9%), sebanyak 99 responden (93.4%) tidak bekerja, mempunyai anak > 2 anak sebanyak 69 responden (65.1%), pendapatan keluarga lebih banyak ≥ UMR sebanyak 87 responden (82.1%), sebanyak 79 responden (74.5%) berpengetahuan baik mengenai ASI eksklusif, dan sebagian besar responden memberikan ASI secara eksklusif.sebanyak 69 responden (65.1%). Berdasarkan variabel persepsi kepercayaan, (susceptibility, severity, benefit, dan barriers), didapatkan nilai p < 0.05, menunjukkan adanya hubungan yang signifikan antara persepsi kepercayaan dengan pemberian ASI eksklusif. Simpulan: Terdapat hubungan yang signifikan antara persepsi kepercayaan ibu dan praktik ASI eksklusif dengan upaya pencegahan stunting.   Kata Kunci: ASI Eksklusif; Kepercayaan; Persepsi; Stunting.